규제정책 비교를 통한 사행산업 영업장 설치 개선 논의: 토토, 복권, 경마 영업장 규제의 차이점 중심으로 - 김종국; 성욱준 (한국비교정부학보, 20(2), 2016)
This study is to analyze the differences in the operating system via a status comparison of the domestic Gaming industry and to discuss the improvement of the industry gambling operations. Ngcc(National gambling control committee) current operations of the gambling industry has a way to foster the installation and operation of the installation and operations directly with the private operator of the gambling industry. The installation of small-scale industries and retailers are operating thousands of locations, industries that operate a large area of ​​several hundred square meter store will be operating dozens of lesser curvature. If there is a strict limit for the installation sector receives some industries are not subject to few restrictions on installation. In addition, these statistics for industry Dealer has been published only horse racing, cycle racing, motorboat racing OTC release place, Toto, Lotto is a state that is not even published yearly basis points for opening, operating locations, such as closed positions. Therefore, the paper industry and recognized the need for a difference in the gambling industry and gambling accurate statistical data related announcement, it proposes the installation and management of an effective way through the Dealer sector benchmarking. KCI Citation Count: 3